Stabilization of 2D Water Films in Porous Triple‐Layer Membranes with a Hydrophilic Core: Cooling Textiles and Passive Evaporative Room Climate Control1 . Issue 8 (24th April 2017) - Stucki, Mario; Stark, Wendelin J.
Abstract : Cooling and climate control are among the largest energy consuming processes in the world. By introducing passive systems, the energy consumption can be shifted to more renewable sources like sunlight. Combining hydrophobic and hydrophilic polymeric matrices in fully porous flat sheet membranes affords a triple‐layer construct able of laterally transport water without energy input, while cooling and wetting the surrounding air by evaporation. In three subsequent coating steps, the material is assembled, the pore‐forming template is released, and the materials are tested on their behavior in a passive cooling application. The straightforward and simple way of combining polymers with opposing chemical properties in a fully porous manner offers a wide range of new applications. Abstract : Combining hydrophobic and hydrophilic polymeric matrices in fully porous flat sheet membranes affords a triple‐layer construct able of laterally transport water without energy input, while cooling, and wetting the surrounding air by evaporation. In three subsequent coating steps, the material is assembled, the pore‐forming template is released, and the materials is tested on their behavior in a passive cooling application.